Bosses, Machines, and Urban Voters - Allswang, John M.; Project Muse; Project Muse. (Project Muse, 2019)
Political machines, and the bosses who ran them, are largely a relic of the nineteenth century. A prominent feature in nineteenth-century urban politics, political machines mobilized urban voters by providing services in exchange for voters' support of a party or candidate. Allswang examines four machines and five urban bosses over the course of a century. He argues that efforts to extract a meaningful general theory from the American experience of political machines are difficult given the particularity of each city's history. A city's composition largely determined the character of its political machines. Furthermore, while political machines are often regarded as nondemocratic and corrupt, Allswang discusses the strengths of the urban machine approach--chief among those being its ability to organize voters around specific issues.
Preface to the 1986 edition -- Of city bosses and college graduates -- William Marcy Tweed: the first boss -- Charles Francis Murphy: the enduring boss -- Big Bill Thompson and Tony Cermak: the rival bosses -- Richard J. Daley: the last boss? -- Black cities, white machines -- Epilogue: Of bosses and bossing.
Originally published: Revised edition. Baltimore, Maryland : Johns Hopkins University Press, [1986].
Issued as part of book collections on Project MUSE.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Politicians -- United States -- History; Municipal government -- United States -- History; Electronic books; Electronic books